REDUCTION OF PRODUCTION CYCLE TIME BY OPTIMISING PRODUCTION AND NON-PRODUCTION COMPONENTS OF TIME IN THE METALWORKING INDUSTRY: A CASE STUDY - Spasojevic Brkic, Vesna K; Klarin, M; Stanisavljev, S; Brkić, A; Sajfert, Z (The South African Journal of Industrial Engineering, 2016)
The production cycle (PC) time, as a very important economic indicator of freezing current assets, involves the time needed to manufacture a unit or a series of units, from putting them into production until they are put into storage; and yet it is rarely discussed in the literature, even though it should be also analysed and be made as short as possible. The goal of this article is to survey and control the methodology of reducing the PC time of components in the metalworking industry, grouped by factor analysis into the factors of production and non-production components, observed by a modified method of current observations, and viewed as a process whose effectiveness was monitored using control charts. The survey is based on data collected through 1,576 observations in a Serbian company that manufactures electrical and electronic equipment for motor vehicles. The 2012 results, when compared with those of 2011, indicate that the PC time is significantly reduced by 93 minutes, or by 28.53 per cent, and the manufacturing time by 46 minutes, or by 19.17 per cent. The results furnish empirical findings that provide insights into a number of managerial issues concerning investment decisions in product-specific cycle time improvements and reductions, together with process redesigns.